Literary Traditions: English in Malaysia and Singapore (Column 2) - Quayum, Mohammad Abdul (The Daily Star, Bangladesh, 2014)
In Malaysia, circumstances changed for writers in English at a precipitous rate as they were soon pushed to the margins of national culture. In 1966, Han Suyin optimistically defined Malaysian literature as “those writings (drama, novel, short story, play and verse), which by emotion, identification, description, social context and involvement relate to Malaysia… whether written in Malay, Chinese, Tamil or English.” But such an inclusive vision of Malaysian literature proved too ambitious as many nationalists became increasingly vocal in their demand that the Malay language should be the only means of expression of Malaysia's national culture. While writers in English argued that a more appropriate path for building the nation was to work towards a Malaysian identity that would reflect the country's multi-ethnic background, writers in bahasa believed that the future citizenry should be moulded on Malaya's traditional culture and heritage, meaning Malay language and Malay culture.....